2017
DOI: 10.1002/adfm.201703674
|View full text |Cite
|
Sign up to set email alerts
|

Theranostic Prodrug Vesicles for Reactive Oxygen Species‐Triggered Ultrafast Drug Release and Local‐Regional Therapy of Metastatic Triple‐Negative Breast Cancer

Abstract: A reactive oxygen species (ROS)-activatable doxorubicin (Dox) prodrug vesicle (RADV) is presented for image-guided ultrafast drug release and local-regional therapy of the metastatic triple-negative breast cancer (TNBC). RADV is prepared by integrating a ROS-activatable Dox prodrug, a poly(ethylene glycol) (PEG)-modified photosensitizer pyropheophorbide-a, an unsaturated phospholipid 1,2-dioleoyl-sn-glycero-3-phosphocholine, and cholesterol into one single nanoplatform. RADV is of extremely high drug loading r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 43 publications
2
51
0
2
Order By: Relevance
“…We developed a multifunctional micelle with efficient production of singlet oxygen upon laser irradiation to improve their deep penetration for enhancement of therapeutic effects . Moreover, the generation of reactive oxygen species (ROS) upon laser irradiation has been used to trigger intra‐tumoral extravasation and deep penetration of liposomes for treatment of triple‐negative breast cancer . Specifically, Xie and co‐workers exploited ferritin nanocages as a photosensitizer carrier with selective targeting of CAFs .…”
Section: Remodeling Of Tumor Stromal Microenvironmentsmentioning
confidence: 99%
“…We developed a multifunctional micelle with efficient production of singlet oxygen upon laser irradiation to improve their deep penetration for enhancement of therapeutic effects . Moreover, the generation of reactive oxygen species (ROS) upon laser irradiation has been used to trigger intra‐tumoral extravasation and deep penetration of liposomes for treatment of triple‐negative breast cancer . Specifically, Xie and co‐workers exploited ferritin nanocages as a photosensitizer carrier with selective targeting of CAFs .…”
Section: Remodeling Of Tumor Stromal Microenvironmentsmentioning
confidence: 99%
“…Therefore, these chemo-photodynamic therapies are simply combinations of the two therapies and do not confer synergistic effects of PS and chemotherapy drugs, making them insufficient for amplifying the anticancer efficacy. Increasing evidence has demonstrated that nanocarriers should boost the intracellular release of cytotoxic drug during the PDT process to yield the maximal benefit of chemo-photodynamic therapy 22 - 27 . Liu et al demonstrated that the mesoporous silica nanorods with SO-sensitive shells offer remarkable synergistic therapeutic effects in cancer treatment owing to the boosted release of DOX specifically at the tumor site during the light-induced PDT process 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Poly‐prodrug nanoparticles of doxorubicin have been constructed. For example, Li and co‐workers developed a prodrug vesicle based on the thioketal linkage for local‐regional therapy of metastatic triple‐negative breast cancer. The system was triggered by light irradiation (producing ROS) for combined chemo‐ and photodynamic therapy.…”
Section: Ros‐activated Drug Delivery and Small‐molecular Prodrug Systemsmentioning
confidence: 99%